Batik Bliss / Muhammad Haziq Mohamed Nazir and Zainul Ariffin Daud - Mohamed Nazir, Muhammad Haziq; Daud, Zainul Ariffin (2023)
Batik Bliss, a venture into food products, specifically “Kek Batik” in Malaysia. Combining the rich heritage of Malaysia with delectable cakes, our venture aims to captivate the Malaysian market with a unique fusion of cultural artistry and indulgent desserts. Malaysia boasts a strong appreciation for traditional crafts and a growing trend in the food and bakery industry, making it an ideal market for our Batik Cake business. By leveraging these factors, we anticipate tapping into a niche market segment and attracting a diverse customer base as we enjoy sweet and savoury food that comes right away and is ready to be served. Our primary target market comprises youngsters, university students, and young adults in Malaysia. This demographic is known for their adventurous palate, openness to new experiences, and enthusiasm for cultural exploration. By offering Batik Cakes, which combine traditional with contemporary desserts, we seek to appeal to their sense of creativity and appreciation for local heritage as well as serve them delightful desserts from the comfort of their home. As a start-up business, we will establish a presence on social media platforms such as WhatsApp and Facebook, utilizing visually captivating content, including quality images of our batik cakes. By showcasing the artistry behind our products and encouraging user-generated content, we aim to generate excitement, encourage social sharing, and increase brand awareness among our target audience. Using those channels, we can easily communicate with our customers through Facebook posts and WhatsApp conversations, where the numbers will be available in the Facebook user description. Furthermore, any inquiries or reviews on the batik cake can be made directly to us. Recognizing the convenience sought by youngsters and young adults, we will provide a user-friendly online ordering platform with seamless payment options. Additionally, we will offer a reliable and efficient delivery service, ensuring that our Batik Cakes reach customers' doorsteps promptly and in perfect condition. To effectively promote our business, we will employ a combination of hard sell and soft sell strategies, tailored to resonate with and tempt our target market, and lay out our business plan and objectives to strategize marketing. The detailed elements and explanations regarding our business and products will be expanded throughout the report.